Household food security and nutrient adequacy amidst COVID-19 pandemic in Nepal. - KC, Dirghayu (2021)
SUMMARY: Pandemic followed by the immediate shutdown throughout the world twirled the world itself upside down. Nearly one in every ten people was exposed to severe levels of food insecurity in the year 2019. These figures are likely to increase with the disruption in agricultural production, supply and labor market following measures taken to combat the crisis. In addition to the health consequences of the virus, measures taken by the government of Nepal to stem the spread of transmission of COVID-19 such as restriction on movement and operation of business and markets have social and economic impact including further exacerbation of food security issues across the country. As pandemic progress present study to be conduct aims to identify the current nutritional adequacy and status of food security among the targeted population and help determine the impact of this pandemic on the livelihood of our target population. The survey also seeks to analyze the bottlenecks and pathways in which food security may have been impacted in certain rural municipalities of our targeted province. The study was cross-sectional descriptive in nature. The COVID-19 crisis triggered multidimensional social and economic impacts which stretched beyond the primary health crisis. This study purposively selected three rural municipalities of Lalitpur sub-metropolitan city. Information was collected on socio-demographic characteristics of the participants; impact of COVID-19 on their income and livelihood, household's access to food and dietary diversity as well as nutrient adequacy. Questionnaire was prepared in Nepali to ensure that questions were understood by the participants. Data compilation, checking, editing and coding was carried out following data collection. Data was systematically coded and entered in Epi Data 3.1 inferential statistics such as chi square test was applied to test the significance of association between independent and dependent variables. Bivariate and Multi-variate analysis were used to show the association between the dependent and independent variable. Socio-demographic characteristics of the participant showed mean age of the participant was found to be 45 years. More than two-third of the total participants were Brahmin with Hindu being 78.7%. Majority of the participants were found to have attended school with one-fifth of them being able to general read and write. Agricultural was found to be the major source of income for almost four- fifth of the population. Only 6.3% of the participating household reported to have major physical and mental disability whereas 13.4% of them reported the presence of chronic diseases in their household. Assessment of household's food security status revealed that 3% of the household being severely food insecure followed by more than one-fifth being mildly food insecure and exactly one-tenth being moderately food insecure. Dietary diversity score calculated that 91.7% of the participating households were found to have high dietary diversity, 8.3% were found to have medium dietary diversity. The mean dietary diversity score of the interviewed households was found to be 6.9(+-1.1). This Result concludes that insecurity that food insecurity was highly prevalent in our targeted site. Despite, the high level of food insecurity dietary diversity was found satisfactory as almost every household were found to have high dietary diversity.